Nilai-nilai Islam dalam Manajemen Pendidikan: Kajian Filosofis Konstruktivistik melalui Pendekatan Systematic Literature Review - Fitriyana, Fitriyana; Gusliana, Evi; Damayanti, Erlian Eka; Desmawati, Desmawati; Pahrudin, Agus; Rahman, Bujang (STKIP PGRI Bandar Lampung, 2025)
This research aims to analyze the reconstruction of Islamic values in education management through a philosophical approach and a constructivist paradigm. Strengthening values such as trust, fairness, sincerity, deliberation, and itqan is becoming increasingly important because management practices in various Islamic educational institutions still show administrative tendencies that ignore spiritual, ethical, and humanistic dimensions. To answer these problems, this study uses the Systematic Literature Review (SLR) method with the PRISMA 2020 model, which selects scientific articles published in 2020–2025 from Google Scholar, Crossref, DOAJ, and Garuda. Of the 72 articles identified, eight met the inclusion criteria and were analyzed through thematic analysis techniques. The results of the study show that Islamic values have a fundamental position in building an educational management paradigm that is not only oriented towards efficiency, but also on the formation of organizational character and spirituality. The values of trust and fairness strengthen the integrity and fairness of decision-making, the values of sincerity and deliberation encourage participation and harmonization of working relationships, while the value of itqan emphasizes the importance of professionalism and quality culture in education governance. The integration of these five values philosophically forms an ontological, epistemological, and axiological framework for Islamic education management that is contextual and adaptive according to the constructivistic paradigm. This research contributes to providing a systematic conceptual mapping of the role of Islamic values in education management, as well as offering a philosophical framework that can be used as a basis for the sustainable development of policies, leadership, and governance of Islamic educational institutions.